Strategies to Maximize Physical Education by Online or Offline Post Pandemic (Media Ilmu Keolahragaan Indonesia, 2022)
Abstract: After the COVID-19 pandemic, Online Sports and Health Physical Education (PE) has become essential for the sustainability of students' fitness and physical activity. However, many PE teachers are not ready to adapt to learning in the current new average era. The learning situation has not fully "recovered", and online learning habits are continuing so that learning cannot be maximized, especially in PE, which uses motion media as the primary media in learning. A strategy is needed to maximize PE's movement learning process and quality education. Several aspects need to be considered to improve the quality of PE learning, including aspects of the curriculum, information technology facilities, and infrastructure, as well as the participation of parents and the community. The article aims to share strategies for improving quality PE learning in any situation (online/offline).Abstract in Indonesia: Pasca pandemi covid-19 Pendidikan Jasmani Olahraga dan Kesehatan (PE) online menjadi penting untuk keberlanjutan kebugaran dan aktivitas fisik siswa. Namun banyak guru PE belum siap dengan adaptasi pembelajaran di era new normal saat ini. Situasi pembelajaran belum sepenuhnya “pulih”, serta kebiasaan belajar daring masih berlanjut sehingga pembelajaran belum bisa maksimal khususnya PE yang menggunakan media gerak sengan media utama dalam pembelajarannya. Diperlukan strategi untuk memaksimalkan proses belajar gerak dan pendidikan yang berkualitas dari PE. Tujuan artikel adalah untuk sharing strategi dalam meningkatkan pembelajaran PE yang berkualitas dalam situasi apapun (online/offline). Ada beberapa aspek yang perlu dipertimbangkan untuk meningkatkan kualitas pembelajaran PE diantaranya yaitu aspek kurikulum, sarana dan prasarana teknologi informasi, serta peran serta orang tua dan masyarakat.